Factors affecting the job performance of academic staff in private universities in Malaysia - Fong, Yin Ling; Loh, Chuan Kit; Loh, Zheng Yu; Tan, Jia Le (2023)
The purpose of conducting this research is to investigate the factors that are affecting the job performance of academic staff in private universities in Malaysia. The factors that may have significant impacts on job performance are work-life balance, job stress, and the working environment. The research was conducted by distributing questionnaires by using Google forms to the target respondents which are academic staff of private universities in Malaysia. In this research, we have collected 346 responses from the target respondents. The data collected from the survey will be analysed using the Statistical Package for the Social Sciences (SPSS) to conduct the pilot study and the full study. Moreover, our research has also used multiple regression analysis to test the significance of the relationship between the dependent variable (job performance) and the independent variables (work-life balance, job stress, and working environment). In this research, the three independent variables (work-life balance, job stress, and working environment) have a significant relationship with the dependent variable (job performance). Thus, the detailed results of the research will be further discussed in the chapters below.